High-Intensity Interval Training’s Effect on Cognitive Functions - Sabita, Rifqi; Siagian, Minarma; Ibrahim, Nurhadi (Indonesian Journal of Multidisciplinary Science, 2023)
HIIT has been known to improve cognitive function. In addition to its effect on the hippocampal area. After HIIT training, BDNF levels also increase in the spinal cord, cerebellum and several cortical areas through increasing levels of Insulin-like Growth Factor-1 (IGF-1). In neurons, BDNF is present not only in the cytoplasm, but also near the dendritic spines, which influences their development. BDNF stimulates the process of neuroplasticity, which is manifested in neurogenesis, stimulation of the plasticity of serotoninergic, dopaminergic, cholinergic or noradrenergic neurons, dendritogenesis, and synaptogenesis. Moreover, BDNF facilitates the growth and survival of neurons and microglial cells. It also participates in cell differentiation, potentiation of signal transmission, induction, and maintenance of long-term potentiation of the synapse enhancement. Because of these properties, BDNF enhances cognition and takes part in emotional processes, spatial orientation and learning, as well as body coordination. Evidence suggests that IGF-1 is a major determinant of the effect of physical exercise on BDNF levels and thus on cognition more generally. There is an upregulation of Fndc5 gene expression in skeletal muscle and an increase in irisin after prolonged resistance training in rats and humans following HIIT training. When hippocampal Fndc5 was upregulated during exercise, BDNF and other neuroprotective genes were also activated in the rat hippocampus. Exercise-induced adult hippocampal neurogenesis is associated with increased Fndc5 and BDNF genes thus enhancing cognition. Then, stroke is associated with neuroinflammation that affects the processes of neuroplasticity in the lesion core, penumbra and small areas such as the spinal cord.